Evaluation of nursing documentation: The experience of nurses from the primary and secondary/tertiary health care (Journal of Health Sciences, 2020)
Introduction: Aim of the study is to piloting nursing documentation to obtain comments based on the experience of nurses/medical technicians from the primary, secondary, and tertiary health care about the documentation before it is published and starts being used.Methods: A questionnaire was designed in the electronic form to be used for the evaluation and suggestions by nurses/medical technicians on the piloted form and content of nursing documentation for all levels of health care. A piloting sample was prepared to make 10% of nurses/medical technicians from health care institutions from the territory of the Federation of Bosnia and Herzegovina.Results: A total of 94.3% of examinees at the primary health care level and only 17.2% of the examinees in the secondary and tertiary health care fill out nursing documentation both manually and electronically. All examinees at all levels of health care understand the purpose and importance of nursing documentation. A total of 27.7% of the examinees at the primary and 40.9% of the examinees at the secondary and tertiary level of health care pointed out that filling out nursing documentation was too time-consuming.Conclusion: A total of 51.2% of the examinees at the primary and 64.2% at the secondary and tertiary level of health care agreed that submitted nursing documentation was adequate for use. It is suggested that after the adoption of nursing documentation at all levels of health care, piloting of its use should be conducted to evaluate the quality and quantity of all nursing documentation.